Analysis of The Efficiency of The Use of Production Factors And Income in Sugarcane Farming (Case Study of Independent Sugarcane Farming in Kedungjajang Sub-District, Lumajang District - Santoso, Djoko Budi; Arvianti, Eri Yusnita; Santosa, Budi (International Research & Development for Human Beings (IRDH), 2025)
This study aims to analyze the efficiency of the use of production factors and income in sugarcane farming (Saccharum officinarum L.) in Kedungjajang District, Lumajang Regency. The sampling was conducted using the Simple Random Sampling technique, involving 110 sugarcane farmers from a total population of 2,191 farmers. The analysis methods used include cost, income, and efficiency analysis (technical, allocative, and economic) with Frontier software version 4.1. The research results show that the total cost of sugarcane farming reaches Rp 40,150,900/Ha/Planting Season with a revenue of Rp 79,412,830/Ha/Planting Season, resulting in a net income for farmers of Rp 39,261,900/Ha/Planting Season. Most farmers (77.28%) have achieved technical efficiency in the interval of 0.95-1.00 with an average of 0.972. Meanwhile, 60% of farmers achieved optimal allocative efficiency and 62.73% of farmers achieved economic efficiency. Factors such as age, education, and farming experience do not significantly affect technical inefficiency. Sugarcane farming at the research location has the potential to be further developed by optimizing the allocation of production inputs such as seeds, fertilizers, herbicides, and labor to maximize farmers' income.